Clinical supervision and support: Perspectives of undergraduate nursing students on their clinical learning environment in Malawi - Stella Kamphinda; Evelyn B. Chilemba (AOSIS, 2019)
Background: The nurse educators' role in clinical learning is to define the necessary prerequisites of an ideal clinical learning environment. Objectives: The purpose of the study was to explore and describe the Kamuzu College of Nursing (KCN) undergraduate nursing students' perspectives on clinical supervision and support in their clinical learning environment and their preferences in the clinical learning environment. Method: A mixed method research approach was used to explore and describe clinical supervision from the students' perspectives on the features of their actual and preferred clinical learning environment. The study's population comprised all third- and fourth-year undergraduate nursing students (n = 219). A sample (n = 125) was randomly selected from the population for the quantitative survey of which 120 questionnaires (96%) were valid for analysis. The data collection for qualitative arm of the study comprised interviews conducted through purposive sampling interviewing 20 participants. Survey results were analysed using the Statistical Package for the Social Science (Version 16) and the qualitative data were analysed using the content analysis approach where themes were generated. Results: The study found that the participants were not satisfied with clinical supervision and support during clinical learning. The participants preferred improved clinical supervision and support in their clinical learning. Comparing the difference between actual and the preferred items of supervision the results were statistically significant at p < 0.05. Conclusion: There is a need to improve students' clinical supervision and support at KCN. Nurse educators need to plan for clinical supervision and support effectively to promote proficient nursing graduates.